Visual Perception of Organic and Polygonal Shapes in the Graphic Communication Processes - Robert Geček; Damir Vusić (Tehnički Glasnik)
Many factors influence the visibility and proper reception of visual messages. The forms used in communication play a crucial yet often overlooked role in this process. This paper investigates which forms are more favourably perceived by the public in graphic communications. A test questionnaire was developed to gauge respondents' preferences for different shapes. The study involved 63 participants whose visual attention to organic and polygonal shapes was measured using an eye-tracker over an 8-second interval. Three scripts were utilized: two freely available ones and one specifically written for this research. These scripts were implemented in MATLAB to analyse and present the visual results of the study. The hypotheses were tested using two statistical methods: the t-test for two vectors and Wilcoxon's rank-sum test. Based on the findings, recommendations were outlined for future research on the application of organic and polygonal shapes in graphic communications.